Aging increases the systemic molecular degree of inflammatory perturbation in patients with tuberculosis - Souza, Deivide Oliveira de (2020)
Intramural Research Program of the NIAID to S.B. and N.P.K. This study was also financed in part by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) (Finance Code 001). The work of B.B.A. was supported by grants from the NIH (U01AI115940, R01AI069923-08, R01AI20790-02), by Intramural Program of Fundação Oswaldo Cruz and by the Brazilian National Council for Scientific and Technological Development (CNPq–bolsa de produtividade 1D). D.O.S. and M.B.A. receive fellowships from the Fundação de Amparo à Pesquisa da Bahia (FAPESB). C.L.V. is a research fellow and K.F.F. is a postdoctoral fellow from CNPq.